Pengendalian, Prinsip TQM, dan Unsur dalam Pengelolaan Mutu Sekolah - Junaidi Ana; Nurul Adha; Nurul Fajri Arifin; Nur Afif (Journal of Mandalika Literature, 2024)
Abstract: School quality control management is an important key to ensuring quality and sustainable education in every educational institution. In this context, planning, implementation, measurement, evaluation, and continuous improvement are the main focus. The importance of quality control in improving the quality of education, both in terms of student achievement and teaching effectiveness, is strongly emphasized. In addition, the active involvement of stakeholders, such as students, parents, teachers, and the community, is considered crucial for the success of quality control. By involving them in decision-making processes and policy implementation, schools can ensure responsiveness to their needs and expectations. With this approach, schools can achieve continuous improvements in the quality of their education in accordance with established standards. The research in this paper uses a descriptive-qualitative approach, using primary and supporting literature to review the existing discussion. In conclusion, school quality control management provides a solid foundation for achieving optimal academic achievement and provides positive benefits for all education stakeholders.